Evaluating the Impact of Various Parameters on the Gamma Index Values of 2D Diode Array in IMRT Verification - Jabbari, Keyvan (J Med Signals Sens, 2018)
BACKGROUND: MapCHECK2 is a two-dimensional diode arrays planar dosimetry verification system. Dosimetric results are evaluated with gamma index. This study aims to provide comprehensive information on the impact of various factors on the gamma index values of MapCHECK2, which is mostly used for IMRT dose verification. METHODS: Seven fields were planned for 6 and 18 MV photons. The azimuthal angle is defined as any rotation of collimators or the MapCHECK2 around the central axis, which was varied from 5 to −5°. The gantry angle was changed from −8 to 8°. Isodose sampling resolution was studied in the range of 0.5 to 4 mm. The effects of additional buildup on gamma index in three cases were also assessed. Gamma test acceptance criteria were 3%/3 mm. RESULTS: The change of azimuthal angle in 5° interval reduced gamma index value by about 9%. The results of putting buildups of various thicknesses on the MapCHECK2 surface showed that gamma index was generally improved in thicker buildup, especially for 18 MV. Changing the sampling resolution from 4 to 2 mm resulted in an increase in gamma index by about 3.7%. The deviation of the gantry in 8° intervals in either directions changed the gamma index only by about 1.6% for 6 MV and 2.1% for 18 MV. CONCLUSION: Among the studied parameters, the azimuthal angle is one of the most effective factors on gamma index value. The gantry angle deviation and sampling resolution are less effective on gamma index value reduction.